2022
DOI: 10.5935/1518-0557.20220023
|View full text |Cite
|
Sign up to set email alerts
|

Serum progesterone on the day of human chorionic gonadotropin (hCG) trigger as a predictor of in-vitro fertilization (IVF) outcome – a retrospective analysis of seven years

Abstract: Objective: To investigate the relationship between progesterone (P4) levels on the day of hCG trigger and IVF outcomes.Methods: This is a retrospective analysis of IVF cycles from January-2013 to December-2019 from a single center. Women (21-39 years) submitted to IVF treatment for various infertility factors were included, while donor oocyte cycles and cancelled cycles were excluded from the study. The primary outcome measure was live birth rate.Results: A total of 2149 cycles were analyzed. Of these, 223 (10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Two studies[ 6 24 ] have reported CLBR as an outcome measure. Seven studies[ 29 30 31 32 33 34 35 ] have evaluated the impact of PPE on the live birth rate in fresh IVF cycles. Five studies have reported the impact on clinical pregnancy rate (CPR)[ 36 37 38 39 40 ] [ Table 1 ].…”
Section: P Remature P Rogesterone ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies[ 6 24 ] have reported CLBR as an outcome measure. Seven studies[ 29 30 31 32 33 34 35 ] have evaluated the impact of PPE on the live birth rate in fresh IVF cycles. Five studies have reported the impact on clinical pregnancy rate (CPR)[ 36 37 38 39 40 ] [ Table 1 ].…”
Section: P Remature P Rogesterone ...mentioning
confidence: 99%
“…However, all the remaining five studies concluded that there was a significant reduction in LBR following fresh transfer in women with PPE on trigger day. [ 29 30 32 34 35 ]…”
Section: P Remature P Rogesterone ...mentioning
confidence: 99%